2017
DOI: 10.3390/chemosensors5030026
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Chemosensory Determination of Cu2+ Using a New Rhodamine–Morpholine Conjugate

Abstract: Abstract:A new rhodamine-B carbonyl-morpholine derivative (denoted as RECM) was prepared by a two-step synthesis procedure. The employed method allowed a lactam ring development of rhodamine-B and ethylenediamine to demonstrate a facile amide bond formation. The obtained RECM was confirmed by 1 H NMR, 13 C NMR, and mass spectrometry analysis. RECM was formed to detect copper ion (Cu 2+ ) due to its problematic toxicity features in aquatic ecosystems. It showed a high selectivity toward Cu 2+ in comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…This may be due to the strong binding tendency of Cu 2+ to replace the Al 3+ ions from the Al 3+ -bounded complex and the paramagnetic quenching properties of Cu 2+ ions. 63,64 A similar experiment for Zn 2+ with H 2 L and other competing ions in DMSO−H 2 O revealed that none of these metal ions exhibited notable fluorescence quenching except for Cu 2+ (Figure 6b).…”
Section: Aggregation-induced Emission Enhancement (Aiee)mentioning
confidence: 72%
See 1 more Smart Citation
“…This may be due to the strong binding tendency of Cu 2+ to replace the Al 3+ ions from the Al 3+ -bounded complex and the paramagnetic quenching properties of Cu 2+ ions. 63,64 A similar experiment for Zn 2+ with H 2 L and other competing ions in DMSO−H 2 O revealed that none of these metal ions exhibited notable fluorescence quenching except for Cu 2+ (Figure 6b).…”
Section: Aggregation-induced Emission Enhancement (Aiee)mentioning
confidence: 72%
“…However, a large decrease in emission intensity was found for Cu 2+ (Figure a). This may be due to the strong binding tendency of Cu 2+ to replace the Al 3+ ions from the Al 3+ -bounded complex and the paramagnetic quenching properties of Cu 2+ ions. , …”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that this probe has a unique ability to recognize Cu 2+ in multi-ion coexistence solutions and shows a very intense fluorescence absorption peak at 525 nm, unlike other ions that are almost unchanged. Compared with other probes reported in the published literature [ 25 , 39 , 40 , 41 , 42 , 43 ], this probe has a relatively low detection limit and a stabilized fluorescence response at pH 6.0–9.0. In addition, through the discussion of the response mechanism between Cu 2+ and the probe, it was revealed that Cu 2+ enabled a certain reversibility of the recognition effect of the N2 probe by opening the lactam ring of the N2 probe and complexing with it in a 1:1 coordination ratio ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 85%
“…Additionally; thienopyrimidine scaffolds with appropriate absorption and emission wavelengths act as fluorophores. [13,14] These fluorescent organic compounds are widely used in bioprobes, [15,16] organic light-emitting diodes, [17,18] photosensitizers, [19] and optical chemosensors, [20][21][22] which become important tools in analytical chemistry and medicine. [23][24][25] Moreover, some fluorescent compounds are utilized in studying the environmental pollution.…”
Section: Introductionmentioning
confidence: 99%